Formulation Of Sheet Mask Preparation Combination Of Moringa Leaves (Moringa Oleifera L.) And Telang Flowers (Clitoria Ternatea L.) And Physical Quality Test - Tria Agustina; Annie Rahmatillah; Rahmat Hidayat (CV. AFDIFAL MAJU BERKAH, 2026)
The Indonesian cosmetics industry is growing rapidly with increasing demand for herbal sheet masks due to premature aging and pollution. The combination of Moringa oleifera L. leaves and Clitoria ternatea L. flowers has antioxidant potential, but formulation studies are limited. To formulate a sheet mask combining infusions of both plants and evaluate its physical quality. Quantitative descriptive study with qualitative observation. The sheet mask formula population, 3 replications per formula and 20 respondents for irritation test. Instruments: pH meter, viscometer, skin analyzer; descriptive analysis and Shapiro-Wilk (SPSS). The formula is stable with a pH of 4.97-5.77, viscosity of 173-266 cps, spreadability of 5.8-6.2 cm, homogeneous, good organoleptic, free from irritation, and increased humidity up to 60%. Data are normal (p > 0.05). The preparation meets the physical quality standards of the Indonesian Herbal Pharmacopoeia, has the potential to be a safe local skincare product.